(untitled) - Hibbing, Jonh R (Cambridge, 2002)
Examining how people want their democratic government to work, this study finds that Americans don't like many of the practices associated with democracy: the conflicts, the debates, the compromises. It finds that Americans don't want to have to see democracy in practice, nor do they want to be involved in politics. If American citizens had their way, political decisions would be made by unselfish decision-makers, lessening the need for monitoring government.
Keywords: Political,Chính trị